Post-cartel pricing during litigation - Joseph E. Harrington (The Johns Hopkins University, Department of Economics, 2002)
Standard methods in the U.S. for calculating antitrust damages in price-fixing cases is shown to create a strategic incentive for firms to price above the non-collusive price after the cartel has dissolved. This results in an overestimate of the but for price and an underestimate of the level of damages. The extent of this upward bias in the but for price is greater, the longer the cartel was in place and the more concentrated is the industry.
Keywords: 330; Kartell; Betriebliche Preispolitik; Konzentrationspolitik; Oligopol; Theorie